1996
DOI: 10.1183/09031936.96.09061257
|View full text |Cite
|
Sign up to set email alerts
|

Response to high frequency jet ventilation may predict the need for extracorporeal membrane oxygenation

Abstract: The aim of this study was to determine predictors of response whilst using high frequency jet ventilation (HFJV) for infants in intractable respiratory failure, in order to avoid the utilization of extracorporeal membrane oxygenation (ECMO). We reviewed patient demographics, ventilator parameters, blood gas values, length of oxygen therapy and use of surfactant and outcome, in infants given a 4 h trial of HFJV as the minimum to eliminate those infants where HFJV is used as a bridge to ECMO. The study was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Additionally, F IO 2 was significantly higher for non-responders during this time, at similar ventilating pressures, which may suggest that these subjects may have benefited from increased PEEP. Furthermore, these findings may suggest that subjects failing HFJV had a more significant oxygenation derangement and are in accordance with those of Stewart et al 15 These authors found that responders to HFJV were characterized by a decrease in oxygenation index at hour 4 (10.7 Ϯ 5.2) compared with (17.6 Ϯ 13.4) in non-responders, without an increase in P aw . Similarly, Baumgart et al 13 reviewed 73 extracorporeal membrane oxygenation-eligible infants of Ͼ34 weeks gestational age who received HFJV secondary to intractable respiratory failure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, F IO 2 was significantly higher for non-responders during this time, at similar ventilating pressures, which may suggest that these subjects may have benefited from increased PEEP. Furthermore, these findings may suggest that subjects failing HFJV had a more significant oxygenation derangement and are in accordance with those of Stewart et al 15 These authors found that responders to HFJV were characterized by a decrease in oxygenation index at hour 4 (10.7 Ϯ 5.2) compared with (17.6 Ϯ 13.4) in non-responders, without an increase in P aw . Similarly, Baumgart et al 13 reviewed 73 extracorporeal membrane oxygenation-eligible infants of Ͼ34 weeks gestational age who received HFJV secondary to intractable respiratory failure.…”
Section: Discussionsupporting
confidence: 81%
“…[13][14][15] In the current study, capillary P CO 2 and pH were studied considering that the majority of subjects (n ϭ 29, 85%) did not have arterial access when HFJV was initiated. A significant reduction in capillary P CO 2 and elevation of pH were observed in the responder group following 1 h of HFJV.…”
Section: Discussionmentioning
confidence: 99%
“…13 Likewise, HFJV has also been found to be very effective in improving oxygenation and ventilation of in pre-ECMO neonates. 5 While HFJV appeared to be better at improving oxygenation and efficiency in gas exchanges than the use of CMV, either immediately after changing ventilator to an HFJV (Table 3) or after the transported neonates reached our unit (Table 2), the values did not reach statistical significance. The iNO-to-CMV connection in our setup instead of the iNO-to-HFJV depends on the ability of the jet flow to entrain gas from the conventional limb.…”
Section: Discussionmentioning
confidence: 73%
“…2 The use of iNO or a high-frequency ventilator has been shown to decrease the need for ECMO, [3][4][5] but consequently, also increases the need to promptly transport nonresponders with the same combination of high-frequency ventilation and iNO to an ECMO center.…”
Section: Introductionmentioning
confidence: 99%
“…First, HFJV was used as a special ventilation mode during diagnostic or surgical procedures in patients with airway pathology [2±5,20±22]. Second, HFJV was employed as a respiratory support technique to improve gas exchange during severe pulmonary failure (Table 1) in infants, children and adults (47%) [7±11, 23,24]. Furthermore, hand-triggered jet ventilation devices served as emergency tools to manage dif®cult airways (`can't intubate, can't ventilate' situations) with intravenous (i.v.)…”
Section: Indicationsmentioning
confidence: 99%